2013
DOI: 10.3892/ijmm.2013.1456
|View full text |Cite
|
Sign up to set email alerts
|

Survivin, a key component of the Wnt/β-catenin signaling pathway, contributes to traumatic brain injury-induced adult neurogenesis in the mouse dentate gyrus

Abstract: The enhancement of endogenous neurogenesis has been suggested in the treatment of traumatic brain injury (TBI); however, the factors that trigger the process of adult neurogenesis following TBI remain elusive. In the adult mammalian central nervous system, there are 2 neurogenic regions: the subgranular zone (SGZ) of the hippocampus and the subventricular zone (SVZ) of the lateral ventricles, both of which maintain relatively quiescent states in a stable microenvironment. However, once stimulated by intrinsic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…25 We concentrated on two areas in the mouse brain; the subgranular layer of the hippocampal DG and the subventricular zone (SVZ) of the lateral ventricle. 26,27 Both these areas of the rodent brain are well known to give rise to neuroprogenitor cells both after TBI 28 and after other interventions that have been tested for possible neuroprotective and neuroregenerative effects. 29,30 The two time points of analysis were 7 days and 28 days after the TBI induction.…”
Section: Brdu-neun Expressionmentioning
confidence: 99%
“…25 We concentrated on two areas in the mouse brain; the subgranular layer of the hippocampal DG and the subventricular zone (SVZ) of the lateral ventricle. 26,27 Both these areas of the rodent brain are well known to give rise to neuroprogenitor cells both after TBI 28 and after other interventions that have been tested for possible neuroprotective and neuroregenerative effects. 29,30 The two time points of analysis were 7 days and 28 days after the TBI induction.…”
Section: Brdu-neun Expressionmentioning
confidence: 99%
“…Other than these increase in gene expression of Wnt-1, nucleolin, mTOR (NT NCs) and PI3K (Tar NCs) MAPK (Tar NCs) was also observed. Since survivin is known to be a key component of both MAPK/ERK and Wnt/β catenin signalling pathway [67,68], activation of these pathways could be the reason for upregulation of survivin in the tumors ( Figure 8B). …”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Moreover, Zhang et al [75] suggested that there is a connection between the expression of survivin and adult neurogenesis. Thus, the observed decrement in survivin expression might be attributed to the decreased neurogenesis due to DA depletion [71] .…”
Section: Discussionmentioning
confidence: 99%